A Study on Multiple Load Conditions Analysis for a Conventional Bicycle vs. a Variable-Chain Stay-Length (VCL) Bicycle De1 - Meor Rashydan, Abdullah; Muhammad Izzat Nor, Ma'arof; Wong, Winson, Zu Xian; Suresh, Akshith; Girma, Tadesse Chala (INTI International University, 2023)
The aim of this study was to study on the multiple loading conditions on a varied bicycle’s chain stay designs. The benchmark for this study was a conventional bicycle chassis design which is available in the market. The specification details of this chassis were obtained from the manufacturer’s website. The new design was a Variable-Chain Stay-Length (VCL) configuration. The purpose for the VCL is to allow room for the cyclist to attach to have an extra space for placing the cargo. The VCL is rated as VCL De1 and was developed in reference to the aforementioned benchmark chassis. Both chassis were developed via the use of Computer Aided Design (CAD). The chassis were then analyzed via Finite Element Analysis (FEA) software for the following loading conditions: (i) Static start-up (ii) Steady pedaling (iii) Vertical loading (iv) Rear wheel braking. The Maximum Equivalent (von Mises) Stress (MPa) recorded for the loading conditions were as follow: (i) Benchmark Chassis: (Condition 1) 117.58MPa, (Condition 2) 120.51MPa, (Condition 3) 235.15MPa, (Condition 4) 99.40MPa, whilst, for the (ii) VCL De1: (Condition 1) 123.43MPa, (Condition 2) 126.24MPa, (Condition 3) 246.85MPa, (Condition 4) 189.13MPa respectively. Adding to this, the safety factor for the aforementioned conditions were also obtained as follow: (i) Benchmark Chassis: (Condition 1) 2.38, (Condition 2) 2.32, (Condition 3) 1.19, (Condition 4) 2.82, whilst, (ii) VCL De1: (Condition 1) 2.03, (Condition 2) 1.98, (Condition 3) 1.01, (Condition 4) 0.13. In short, the assessments were a success. It could be noted that the safety factors for the VCL De1 is above 1.0 for Condition 1 to 3, yet, at condition 4 is rated at 87% below the Safety Factor. Hence, this result is indeed undesirable. Thus, the VCL De1 is not suitable for usage due to the high possibility of structural failure. Further improvement on design iteration is warranted for the VCL chassis